Erythropoietin‐enhanced endothelial progenitor cell recruitment in peripheral blood and renal vessels during experimental acute kidney injury in rats. (28th January 2016) - Cakiroglu, Figen; Enders‐Comberg, Sora Maria; Pagel, Horst; Rohwedel, Jürgen; Lehnert, Hendrik; Kramer, Jan
Abstract: Beneficial effects of erythropoietin (EPO) have been reported in acute kidney injury (AKI) when administered prior to induction of AKI. We studied the effects of EPO administration on renal function shortly after ischemic AKI. For this purpose, rats were subjected to renal ischemia for 30 min and EPO was administered at a concentration of 500 U/kg either i.v. as a single shot directly after ischemia or with an additional i.p. dose until 3 days after surgery. The results were compared with AKI rats without EPO application and a sham‐operated group. Renal function was assessed by measurement of serum biochemical markers, histological grading, and using an isolated perfused kidney (IPK) model. Furthermore, we performed flow cytometry to analyze the concentration of endothelial progenitor cells (EPCs) in the peripheral blood and renal vessels. Following EPO application, there was only a statistically non‐significant tendency of serum creatinine and urea to improve, particularly after daily EPO application. Renal vascular resistance and the renal perfusion rate were not significantly altered. In the histological analysis, acute tubular necrosis was only marginally ameliorated following EPO administration. In summary, we could not demonstrate a significant improvement in renal function when EPO was applied after AKI. Interestingly, however, EPO treatment resulted in a highly significant increase in CD133‐ and CD34‐positive EPC both in the peripheral blood and renal vessels.